Diversity rules OK! the changing nature of families (Bendigo, Victoria : Video Education Australasia, 2002)
Summary : This program covers the different family types, how families have changed in size and structure over the years, the reasons for those changes, future family trends and the challenges that those trends will present to the current generation.
Executive producer, Neil Barret ; editor, Conrad Trenton
Narrator : Andrea Waycott
Keywords: Family; Family demography; Family relationships